Strategies for Preserving Sasirangan and Planting Local Wisdom Values of Sasirangan Motifs in Schools in Banjarmasin, Indonesia - Melly Agustina Permatasari; Tri Marhaeni Pudji Astuti; Dewi Liesnoor Setyowati; Ersis Warmansyah Abbas (Universitas Negeri Semarang, 2023)
Sasirangan as a regional cloth for the City of Banjarmasin, South Kalimantan, has various Sasirangan motifs that contain local wisdom values ​​that are believed by the community. The purpose of this study was to analyze the preservation of Sasirangan and the inculcation of local wisdom values ​​of the Sasirangan motif in schools. This research uses a qualitative approach with descriptive methods. The research locations are in the city of Banjarmasin and SD Negeri Sungai Jingah 7 Banjarmasin. The informants of this study were Sasirangan craftsmen, school principals and teachers of Sungai Jingah 7 Elementary School, Banjarmasin. Collecting data through observation, interviews, and documentation. Research data analysis techniques are thematic, textual, contextual and interpretive. The results of the research show that the strategy for preserving Sasirangan in the city of Banjarmasin is by wearing Sasirangan clothes every Thursday, incorporating Sasirangan material in local content subjects, participating in Bassirangan parades and exposing en masse during the Banjarmasin Sasirangan Festival (BSF) which is held every year in the city of Banjarmasin. The local wisdom values ​​of the Sasirangan motif in the form of life skill values ​​can be instilled in schools by providing examples or examples, habituation, advice and motivation to students which is carried out every day in class and at school.